Assessment of exercise re-training in chronic low back pain patients in Sub-Saharan Africa: an experimental cohort study using indirect measurement of VO2max - Tiaho, Yirozounlomian; Gandema, Salifou; Zabsonre/Tiendrebeogo , Wendlassida Joelle Stéphanie; Sougue, Charles; Nikiema, Germain; Kaboré, Fulgence; Ouedraogo, Dieu-Donné (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Exercise training is recommended for patients with chronic low back pain. The aim of this study was to evaluate exercise training in patients with chronic low back pain by indirect measurement of VO2max. Patients and methods: This was an experimental cohort study involving 92 patients with chronic low back pain over a two-month period from 5 December 2023 to 5 February 2024. The patients underwent a four-week exercise training programme. Results: The mean age of the patients was 49.37±12.72 years, with extremes of 26 and 70 years. There was a significant improvement in VAS pain intensity (m before=66.6 ± 1.4 ; m after =12 ± 10.9 p=0.0000) and also a significant improvement in VO2 max (m before=25.87 ± 10.15 m after = 28.25 ± 10.64 p= 0.000). The risk factors associated with low VO2max were age over 60 (p=0.000; RR=3), obesity (p=0.0002; RR=2.41) and sedentary lifestyle (p=0.0008; RR=8.39). Conclusion: Indirect measurement of VO2max is effective for evaluating exercise training in patients with chronic low back pain. Our experimental exercise training protocol resulted in a significant improvement in patients' pain and VO2max.